Sifat Mekanis Geopolimer Ringan Berbahan Dasar Fly Ash Batubara Dengan Penambahan Semen Portland Dan Cairan Alkali Aktivator - Reski, M.; Amri, Amun; Helwani, Zuchra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Geopolymer is an inorganic polymer material composed of Si and Al atoms arranged in a 3dimensional network (Si-O-Al) synthesized from aluminosilicate with an alkaline activator solvent. The use of this geopolymer can be used as a material for making lightweight concrete types of cellular lightweight geopolymer (CLG) which can be used as a construction wall for building blocks and brick red brick. This study aims to make a lightweight geopolymer based on fly ash coal using a foaming agent with the addition of sand, portland, and alkaline liquid activators and study the effect of adding cement Portland, and the amount of alkaline liquid activator on the mechanical properties of the resulting mild geopolymer. Making light geopolymers begins with preparing an alkaline activator solution made by mixing 10 M NaOH into sodium silicate with a ratio of (Na2SiO3 2.5/NaOH) to homogeneous, then the foaming liquid is made by dissolving the foaming agent using water with a ratio (foaming agent/water) 1:30, after which the foaming liquid is connected to the foam generator to produce the desired foam, then the process of mixing the raw material used is homogeneous. The mechanical geopolymer mechanical properties test results showed that the highest compressive strength of 2.15 MPa was obtained from variations in the amount of activator liquid 23% with the addition of 15% OPC, the lowest porosity 27.55% obtained from variations in the amount of liquid activator 23% with the addition of 15% OPC. Keywords: fly ash, geopolymers, light geopolymers, liquid activator, OPC